2013
DOI: 10.1016/j.jaac.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination and Implementation of Evidence-Based Practices for Child and Adolescent Mental Health: A Systematic Review

Abstract: Objective While there has been a dramatic increase in the number of evidence-based practices (EBPs) to improve child and adolescent mental health, the poor uptake of these EBPs has led to investigations of factors related to their successful dissemination and implementation. The purpose of this systematic review was to identify key findings from empirical studies examining the dissemination and implementation of EBPs for child and adolescent mental health. Method Out of 14,247 citations initially identified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
192
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(203 citation statements)
references
References 111 publications
6
192
0
2
Order By: Relevance
“…Similar results have been reported elsewhere (e.g. Simonsen et al, 2012;Payton et al, 2008;Sklad, Diekstra, Ritter, Ben, & Gravesteijn, 2012;Durlak et al 2011;Kidger, Araya, Donovan, & Gunnell, 2012;Wells, Barlow, & Stewart-Brown, 2003;Basch, 2011;Novins, Green, Legha, & Aarons, 2013;Weissberg, Goren, Domitrovich, & Dusenbury, 2013). However, despite the large number of school-based programs that foster positive mental health, there continues to be little evidence available concerning how schools measure the implementation of such programs and the impact that they may have (Adelman & Taylor, 2000;Domitrovich et al, 2008;Durlak and DuPre, 2008).…”
Section: Introductionsupporting
confidence: 91%
“…Similar results have been reported elsewhere (e.g. Simonsen et al, 2012;Payton et al, 2008;Sklad, Diekstra, Ritter, Ben, & Gravesteijn, 2012;Durlak et al 2011;Kidger, Araya, Donovan, & Gunnell, 2012;Wells, Barlow, & Stewart-Brown, 2003;Basch, 2011;Novins, Green, Legha, & Aarons, 2013;Weissberg, Goren, Domitrovich, & Dusenbury, 2013). However, despite the large number of school-based programs that foster positive mental health, there continues to be little evidence available concerning how schools measure the implementation of such programs and the impact that they may have (Adelman & Taylor, 2000;Domitrovich et al, 2008;Durlak and DuPre, 2008).…”
Section: Introductionsupporting
confidence: 91%
“…Because relevant primary studies, systematic reviews, and meta-analyses are spread across numerous peer-reviewed journals, the gray (unpublished) literature, and research repositories, the use of prevention interventions by clinicians and health service policymakers may have been hampered by lack of access to what is known about effective interventions. [22][23][24] Therefore, we conducted this overview of systematic reviews (OSRs) of prevention interventions for child and adolescent anxiety. Three questions were addressed: (1) Does the intervention prevent anxiety diagnosis and/or reduce anxiety symptoms compared to passive controls?…”
Section: Introductionmentioning
confidence: 99%
“…Children seen in clinical practice often have more complex and severe disorders, greater levels of comorbidity as well as more adverse psycho-social backgrounds compared to participants in intervention trials who may be selected to avoid comorbidity and are often recruited from non-clinical environments (Weisz et al, 2013). This leads to heated debates about the extent to which evidence-based interventions can be applied to routine service provision (Kazdin, 2008;Novins et al, 2013;Weisz et al, 2013). Deighton et al (2015), using naturalistic service collected data reported no significant difference in outcome between evidence based practice and non-evidence based practice in children with conduct disorders, but a significantly greater improvement according to child self-report among children with emotional disorders.…”
Section: Discussionmentioning
confidence: 99%